Legal Protection for Consumers in the Online Purchase of Personal Health Devices - Sulaiman, Lutfi Yustyanto; Khayru, Rafadi Khan; Darmawan, Didit (Journal of Social Science Studies, 2024)
This literature study examines the legal framework for consumer protection regarding the online sale of personal health devices in Indonesia. Employing a normative juridical analysis, the research investigates the construction of business actor responsibility, the implementation of information obligations, and the effectiveness of dispute resolution mechanisms. The findings indicate that the legal framework is built on a convergence of three regimes: general consumer protection law, health sector regulations, and electronic transaction laws. While normatively comprehensive, the study identifies significant implementation gaps. The obligation to provide complete and honest information, including the display of distribution permits, is often unfulfilled in digital marketplaces. The complexity of the supply chain obscures clear accountability, and dispute resolution through the Consumer Dispute Settlement Agency (BPSK) or courts faces major procedural and evidentiary hurdles, particularly for proving device inaccuracy or health-related losses. The study concludes that strengthening protection requires specific technical regulations for online health device sales, enhanced verification and monitoring roles for e-commerce platforms, improved capacity of BPSK to handle technical disputes, and increased consumer literacy regarding health product safety in the digital marketplace.